2020
DOI: 10.1021/acs.chemrestox.9b00524
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Lixisenatide against Lipopolysaccharide-Induced Inflammation Response in MAC-T Bovine Mammary Epithelial Cells: A Therapeutic Implication in Mastitis

Abstract: Mastitis is acute inflammation caused by microbial infections in the mammary glands. This disease is extremely harmful to lactating mothers. The preferred clinical strategy is antibiotic treatment, but this method results in resistance and side effects. Lixisenatide, a kind of glucagon-like peptide-1 (GLP-1) receptor agonist, is typically used for the treatment of type II diabetes. It is unknown whether lixisenatide possesses a beneficial role in mastitis. In the current study, we assessed the protective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although recent publications indicate that TNF-α is associated with an LPS-induced inflammatory response, Günther et al, (2009) [9] could not identify TNF-α as one of the top 20 up-regulated genes in their pbMEC studies. However, studies are contradictory: TNF-α detection was possible in experiments with the LPS-stimulated cell line MAC-T [12][13][14]. Lind et al (2015) [11] showed a TNF-α baseline and, in addition, a LPS-dependent TNF-α expression in primary cells using a teat explant model.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent publications indicate that TNF-α is associated with an LPS-induced inflammatory response, Günther et al, (2009) [9] could not identify TNF-α as one of the top 20 up-regulated genes in their pbMEC studies. However, studies are contradictory: TNF-α detection was possible in experiments with the LPS-stimulated cell line MAC-T [12][13][14]. Lind et al (2015) [11] showed a TNF-α baseline and, in addition, a LPS-dependent TNF-α expression in primary cells using a teat explant model.…”
Section: Discussionmentioning
confidence: 99%
“…LPS usually was used to construct an inflammatory model. The construction of mastitis model of cows was frequently based on 1 μg/mL LPS stimulation for BMECs in vitro in many studies [ 33 , 34 , 35 , 36 , 37 ]. There were some studies which reported that a lower concentration of LPS, such as 0.1 [ 38 , 39 ], 0.2 [ 40 , 41 ], 0.5 [ 42 ] μg/mL and so on, could also induce inflammatory responses of BMECs.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent publications indicate that TNF-α is associated with an LPS-induced in ammatory response, Günther et al, (2009) [11] could not identify TNF-α as one of the top 20 up-regulated genes in their pbMEC studies. However, studies are contradictory: TNF-α detection was possible in experiments with the LPS-stimulated cell line MAC-T [14][15][16]. Lind et al (2015) [13] showed a TNF-α baseline and, in addition, a LPS-dependent TNF-α expression in primary cells using a teat explant model.…”
Section: Discussionmentioning
confidence: 99%